Vertebral Osteomyelitis Secondary to Pneumococcal Infection - Bindu Gandrapu; Preeyanka Sundar; Paula Aucoin (Case Reports in Infectious Diseases)
Vertebral osteomyelitis secondary to pneumococcal infection is an uncommon condition caused by Streptococcus pneumoniae. Fever, back pain, and raised ESR are common features in the clinical setting. We report a 62-year-old female patient who presented with an unusual presentation. Later on, vertebral osteomyelitis secondary to pneumococcal infection was confirmed at T8, 9 by CT scan, MRI, and cytology. The patient was treated successfully with high-dose ceftriaxone.